Characterization of Newcastle disease virus (NDV) isolated from NDV vaccinated broiler farms and investigation of vaccine efficacy against challenge with Velogenic genotype VII NDV - Shahrestani, Kiarash Roohani (2014)
Vaccines to control Newcastle disease (ND) were introduced more than 60 years ago. Despite that, ND is still one of the most significant avian diseases affecting major poultry farms in various countries. Class II of Newcastle disease viruses (NDV) can be divided into 10 different genotypes based on the F gene. However, since 1990s genotype VII NDV is the predominant velogenic NDV circulating in South-East Asia causing outbreaks even in well vaccinated flocks. Various factors such as inappropriate vaccination scheme,concurrent infections, immunosuppression and presence of variant NDV have been implicated as the probable causes of the outbreak. The current NDV vaccines comprised of genotype I and/or II viruses. Through the use of reverse genetic technology, genotype–matched NDV vaccine has been used in certain countries. However, the efficacy of this vaccine against the circulating velogenic genotype VII NDV is not well characterized. This study focused on the isolation and characterization of velogenic NDV from NDV vaccinated chickens in Malaysia. Sequencing and phylogenetic analysis based on the F gene of five NDV isolates (IBS001 to IBS005) showed that the viruses belong to genotype VII and sub-genotype VIId of NDV, with F cleavage site motif of 112RRRKRF117. In addition, sequencing of the Cterminus of the HN gene revealed that, viruses lack extension and encoded a typical amino acid sequence length of virulent NDV. Hence, molecular characterization based on the F and HN genes indicated the viruses (IBS001 to IBS005) belong to velogenic genotype VII NDV. One of the isolates, IBS002, was further characterized based on sequencing of the complete length of F and HN genes and pairwise comparisons between different genotypes. A maximum distance was detected between IBS002 and LaSota with nucleotide/amino acids variation between 17.71% to 18.67% for F gene and 20.89% to 23.37% for HN gene. Nucleotide/amino acids variations of 8.79% to 9.77% for F gene and 9.17% to 11.60% for HN genes were detected between isolate IBS002 and genotype VII Dalguban N+ vaccine. In addition, IBS002 has a mean death time (MDT) of 51.2 hours and intracerebral pathogenicity index (ICPI) of 1.76, further confirming that the virus is a velogenic strain. Both genotype matched (Dalguban N+) and mismatched (LaSota and Avinew) vaccines induced 100% protection against mortality and severe clinical symptoms following challenge with 105 ELD50 of IBS002. Vaccinated chickens also showed significant (P<0.05) lower pathogenicity scores although there was no significant (P<0.05) difference among the vaccinated groups. However, sentinel birds of Avinew and Dalguban N+ groups showed lower pathogenicity score compared to sentinels in LaSota group (P<0.05). Furthermore, Avinew and Dalguban N+ vaccinated chickens shed significantly (P<0.05) less virus after challenge and the viral load decreased faster than LaSota group. Moreover, sentinel birds mortality in LaSota vaccinated and non-vaccinated groups were significantly (P<0.05) higher than Avinew and Dalguban N+ vaccinated groups suggesting the importance of genotype matched vaccine (Dalguban N+) and enteric based NDV vaccine (Avinew) in inducing vaccine induced immunity. Vaccine that matched with the hemagglutination-inhibition (HI) test’s antigen induced significantly (P<0.05) higher antibody compared to vaccine from other genotypes where a 2 Log2 difference were detected when genotype VII and genotype II NDV antigens were used to detect homologous and heterologous HI titters. Immunophenotyping study showed significant increased (P<0.01) in KUL-1+ macrophages in PBMCs and splenocytes of control challenged birds. On the other hand, CD3+/CD4+ and CD3+/CD8+ T cells in spleen of different vaccinated groups were increased upon challenge suggesting the possible involvement of these cells in curtailing virus replication. In conclusion, isolated NDVs were classified as velogenic strains and belonged to genotype VIId of class II of NDV. Both genotype matched and mismatched NDV vaccines were able to confer protection against challenge with velogenic genotype VII NDV. However, genotype matched and enteric based NDV vaccines seems to be able to confer a more complete protection against virus shedding and transmission to susceptible chickens following challenged with velogenic genotype VII NDV.